2021
DOI: 10.21833/ijaas.2021.09.006
|View full text |Cite
|
Sign up to set email alerts
|

The role of electronic information resources in supporting scientific research at Northern Border University

Abstract: This study aimed to realize the impact of Electronic Information Resources on the scientific research movement at the Northern Border University. As it includes Electronic Information Resources provided by the university through the Saudi Digital Library, and many forms of sources such as databases, which include full-text databases, abstracts databases, bibliographic databases, as well as electronic books and electronic periodicals, these resources are characterized by the magnitude of content, continuous mod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 14 publications
0
6
0
Order By: Relevance
“…Researchers, teaching staff, and students use EIRs for various purposes, such as academic purposes (i.e., course works, completing assignments, research, compiling teaching and learning materials, preparing seminar presentations, and disseminating and preserving research findings), acquiring development ideas, communicate and collaborate with friends and classmates, improve knowledge, online registration, materials for a writing project, career development, efficient retrieval of information, curriculum design, and recreation. 5,15,[19][20][21][22][23][24][25][26] Electronic information resources in academic libraries are essential to researchers, teaching staff, and students because they provide a comprehensive and vast amount of information that users can quickly and cheaply access in electronic forms in its latest form: 5,10,27 it helps users to advance their research work; 28 it is readily available as long the users have access to the network or internet connectivity; 4 flexible in terms of storage and interoperable since they are dynamic resulting into the wide dissemination of information; convenience since a piece of data can be easily searched, 5,6 EIRs can easily and simultaneously be accessed by multiple off-campus users in a short period; 8 EIRs are up-to-date, trustworthy, and appropriate, access a wide variety of information, and the time and location of access are unlimited and unrestricted and saves physical spaces. 6,29 Mollel and Mwantimwa (2019) 13 observed that library EIR usage depends on the relevancy of the content and users' skills to navigate the different electronic resource platforms, search engines, and interfaces.…”
Section: Use Of Eirs In Academic Librariesmentioning
confidence: 99%
See 3 more Smart Citations
“…Researchers, teaching staff, and students use EIRs for various purposes, such as academic purposes (i.e., course works, completing assignments, research, compiling teaching and learning materials, preparing seminar presentations, and disseminating and preserving research findings), acquiring development ideas, communicate and collaborate with friends and classmates, improve knowledge, online registration, materials for a writing project, career development, efficient retrieval of information, curriculum design, and recreation. 5,15,[19][20][21][22][23][24][25][26] Electronic information resources in academic libraries are essential to researchers, teaching staff, and students because they provide a comprehensive and vast amount of information that users can quickly and cheaply access in electronic forms in its latest form: 5,10,27 it helps users to advance their research work; 28 it is readily available as long the users have access to the network or internet connectivity; 4 flexible in terms of storage and interoperable since they are dynamic resulting into the wide dissemination of information; convenience since a piece of data can be easily searched, 5,6 EIRs can easily and simultaneously be accessed by multiple off-campus users in a short period; 8 EIRs are up-to-date, trustworthy, and appropriate, access a wide variety of information, and the time and location of access are unlimited and unrestricted and saves physical spaces. 6,29 Mollel and Mwantimwa (2019) 13 observed that library EIR usage depends on the relevancy of the content and users' skills to navigate the different electronic resource platforms, search engines, and interfaces.…”
Section: Use Of Eirs In Academic Librariesmentioning
confidence: 99%
“…Skills for information retrieval and evaluation are essential for the optimal utilisation of EIRs. 10 To effectively use EIRs for teaching, learning and carrying out research in the era of information explosion, one must possess a set of skills for defining the problem at hand, identifying the right source of information, retrieving accurate, relevant, and recently published reports. 41,42 The required skills for utilising EIRs have been elaborated on in many studies and must be tackled to better search, retrieve, evaluate, and use the articles.…”
Section: User Competence and Skillsmentioning
confidence: 99%
See 2 more Smart Citations
“…On the other hand, digital content has a role in digitizing information, making the contents smooth and easy to access and process through which learners take a set of procedures to transform the traditional educational content of the digital image over the Internet into content that includes interactive multimedia, including texts, pictures, graphics, shapes, sounds, videos, and animations (Chang, 2008;Al-Sawy, 2021). Digital content allows learners to learn and access information quickly and through a considerable number of them and with high flexibility of time and geographical location.…”
Section: Introductionmentioning
confidence: 99%